PENGARUH KOMISARIS INDEPENDEN DAN KARAKTERISTIK KOMITE AUDIT TERHADAP PENGUNGKAPAN PENGENDALIAN INTERNAL - Paris Halomoan; Totok Dewayanto (Diponegoro Journal of Accounting, 2018)
This study aims to exmine the effect of independent commissioner, audit committee expertise and audit meeting as independent variable toward internal control disclosure as dependent variable. This study uses secondary data obtained from the Indonesia stock exchange (idx). This research using a sample as many as 336 manufacturing companies registered in BEI year 2014 – 2016. The methods used in this research is purposive sampling method. Statistical techniques used in this study is a multiple regression. The results obtained from this research shows independent commissioner, audit committee expertise and audit committee meeting have a significant positive influence on internal control and disclosure.